HUBUNGAN PERAN ORANG TUA DAN BUDAYA DENGAN PENGETAHUAN KESEHATAN REPRODUKSI PADA REMAJA PUTRI DI SMK MUHAMMADIYAH 6 JAKARTA - Kandia Dwi Sartika Putri (2021)
Adolescents is a period where many changes appear, including in terms of reproduction, it is important for adolescents to have good knowledge in reproductive health. The role of parents and culture can affect the knowledge of adolescent's reproductive health. This study aims to determine the relationship between the role of parents and culture with knowledge of reproductive health in adolescent girls at SMK Muhammadiyah 6 Jakarta. The method used is analytic observational with a cross-sectional design. The sampling technique used probability samples technique with a total sample of 141 adolescents. Data analysis used was univariate analysis and bivariate analysis with Chi Square test. The results of this study indicate that there is a relationship between the role of parents and knowledge of reproductive health (p value = 0.017) and there is a relationship between culture and knowledge of reproductive health (p value = 0.032). Adolescents should feel open with their parents and not feel embarrassed when telling their reproductive problems.